2021
DOI: 10.3390/coatings11121563
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Cu-Ag Alloy Films at n-Si(001) and Polycrystalline Ru Substrates

Abstract: Electrodeposition of Cu-Ag films from acidic sulfate bath was conducted at n-Si(001) and polycrystalline Ru substrates. Significant nucleation overpotential of 0.4 V is observed with the Cu-Ag bath at n-Si(001) substrate, whereas the electrodeposition of Cu-Ag at Ru substrate is influenced by Ru oxides at the surface. Incomplete coverage of Si substrate by Cu-Ag deposit was observed from the deposition systems without Ag(I), or with 0.1 mM Ag(I), comparing with the compact Cu-Ag film obtained with the depositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
(88 reference statements)
0
7
1
Order By: Relevance
“…Despite the complications in its derivations (see Appendix A and Appendix D of this commentary), the mean-field solution of the potentiostatic transient from growing nuclei formed at the same time shows a good agreement with the instantaneous mode of the S-H model. 6 However, as observed in our works, the S-H model cannot satisfactorily explain the potentiostatic transients 7 and the spatial distribution 7,8 of electrodeposited Cu-Ag grains. Recently, Ustarroz et al observed that the nucleation and growth can follow "nonclassical" pathways via aggregation of existing nuclei, instead of the concept of nucleation exclusion zones.…”
contrasting
confidence: 56%
“…Despite the complications in its derivations (see Appendix A and Appendix D of this commentary), the mean-field solution of the potentiostatic transient from growing nuclei formed at the same time shows a good agreement with the instantaneous mode of the S-H model. 6 However, as observed in our works, the S-H model cannot satisfactorily explain the potentiostatic transients 7 and the spatial distribution 7,8 of electrodeposited Cu-Ag grains. Recently, Ustarroz et al observed that the nucleation and growth can follow "nonclassical" pathways via aggregation of existing nuclei, instead of the concept of nucleation exclusion zones.…”
contrasting
confidence: 56%
“…The experimental data used in this paper is from the dataset of our previous works [65][66][67] with the potentiostatic transients from our previous work [65]. Before deposition, the n-Si(001) wafer pieces (heavily-doped, resistivity < 0.005 Ω⋅cm) were cleaned in methylene chloride, acetone, and ethanol for 20 min in each step, and then etched in 30% HF solution for 2 mins, followed by rinsing in Milli-Q water.…”
Section: Methodsmentioning
confidence: 99%
“…The Scanning Electron Microscopy (SEM) images used in this paper are from the dataset of our previous works [28][29][30]. A heavily As-doped H-terminated n-Si(001) wafer with a resistivity < 0.005 Ω • cm (Silicon Quest International, San Jose, CA, USA) was cut and then cleaned with methylene chloride, acetone, and ethanol.…”
Section: Methodsmentioning
confidence: 99%